HUMAN AFFECTION IN JOJO MOYES' ME BEFORE YOU - Abdul Razak, Rizka Fadhilah; Mogea, Tini; Maukar, Merlin M. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of this study is to reveal about human affection reflected in Jojo Moyes' Me Before You. This study will be delimited only in revealing about the human affection through Will Traynor and Louisa Clark reflected in the novel written by Jojo Moyes' Me Before You. In this research the writer used qualitative method in analyzing the novel. The Writer used two kinds of sources in collecting the data in this research. That is primary source and secondary sources. There are 3 things that each represent Louisa and Will's affection, in Louisa's character there are emotions, social relationships and caring, while in Will's character there is sincerity, high responsibility and courage which is motivated by how Will is finally able to respond to everything. Based on the results of the analysis in chapter 4, the representation of Will's character who has full of affection is influenced by social environmental factors, characters with strong personalities around him and Will's mental strength who has succeeded in overcoming all his negativity, both lack of confidence, closedness and even temperament, all of them it slowly changed because of Louisa's figure who enabled Will's power of love to fix everything that Will had regretted before. Louisa, who is also the main character in this novel, comes with a social background that is opposite to Will. Her sincerity in serving Will as her employer makes Louisa love and love Will more and more as an important person to her.